MANAJEMEN RISIKO KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PROYEK PEMBANGUNAN CIPUTRA WORLD JAKARTA - I Wayan Wiyasa; I G. A. Adnyana Putera; Mayun Nadiasa (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2015)
Abstract :Generally, in Indonesia the subject of Occupational Health and Safety is often forgotten. This is proven with the high number of work accidents in Indonesia. In 2011, there were 99.491 incidents or on average 414 work accidents cases per day. In 2010 there were 98.711 work accidents, 96.314 cases in 2009, 94.736 cases in 2008 and 83.714 cases in 2007. This reserch is intended to asses the possible major risk of Occupational Health and Safety for The Ciputra World Jakarta building Project, and offer solutions to deal with any unexpected risk. This research was conducted with a descriptive and qualitative method. Survey was carried out to get opinions from respondents on Occupational Health & Safety risks during the construction of the Ciputra World Jakarta. There are Seventy eight (78) high risks were identified with the most being Tower Crane operation job, installation of steel column, beam, and wall with 5 risks. The 2 extreme risks were found in column casting and screeding exterior wall with 1 risk. Suggestion given is to organise training relation to Occupational Health and Safety risk to every employee, introduve shift system, allocate alternate day off to employees, provide health/medical check up, and eliminate high risk and dengerous work environment.